Arsitektur Bugis-Makassar dalam Museum Sejarah Islam: Studi Kasus Desain konsep Vernakular di Makassar - Jasri, Muhammad; Marwati, Marwati; Amin, Burhanuddin (The Department of Architecture, Faculty of Science and Technology, Universitas Islam negeri Alauddin Makassar, 2026)
Makassar possesses significant Islamic historical heritage; however, its museums have not fully represented local culture and identity, as evidenced by declining visitor numbers and limited educational facilities. This study aims to design the Islamic History Museum using a Bugis-Makassar vernacular architectural approach, integrating traditional cultural values, local symbolism, and sustainability principles. A qualitative, descriptive method was employed, including interviews with local leaders and community members, field observations of traditional architecture and environmental conditions, and a literature review on vernacular architectural principles and sustainable building design. Data were analysed through triangulation to develop a contextual, adaptive, and environmentally responsive design concept, which was then visualised through initial sketches and three-dimensional modelling. The results indicate that applying vernacular architecture enables the museum to reflect Bugis-Makassar cultural identity through building form, site orientation, the use of local materials, natural ventilation and lighting, and traditional ornamentation. This approach produces a building that is aesthetically pleasing, functional, energy-efficient, and supportive of social interaction and cultural activities. Consequently, the museum functions not only as a repository of historical artefacts but also as an interactive, educational public space that adapts to modern needs while upholding sustainability principles.